Grammatical interference in written papers translated by Russian and American students - Alexandra Galkina; Alexandra V. Radyuk (Peoples' Friendship University of Russia (RUDN University), 2019)
Language interference is one of the most common problems in foreign language teaching. Language learners inevitably apply knowledge of their native language to a second language, which leads to linguistic interference. The more differences there are between the two languages, the more prominent the interference between them will be. This paper examines the key issues faced by Russian students learning English and English-speaking students learning Russian and suggests key areas of teaching needed in both disciplines.